Vector Spherical Harmonics for Data‐Assimilative Neutral Wind Estimation - Aurora López Rubio; Seebany Datta‐Barua (Space Weather)
Abstract In this work we enable the data assimilation algorithm Estimating Model Parameters from Ionospheric Reverse Engineering (EMPIRE) to estimate global neutral winds. EMPIRE corrects the ion drifts and neutral winds from background models using electron density in the F region derived mainly from total electron content measurements. The new EMPIRE basis functions for the neutral winds are vector spherical harmonics, enforcing the field to be smooth and continuous globally. Global basis functions allow us to estimate the horizontal wind vector from time‐varying plasma densities. The geomagnetic storm on 25 October 2011 is studied to investigate the global implementation of neutral wind estimation. During this storm, the estimates are also compared to those of the old method of estimation using power series and to Fabry‐Perot interferometer (FPI) measurements for validation at three different sites: Pisgah, Cariri, and Nasca. The new global estimation is 10%–20% closer to the FPI measurements than the model and than the old method for most of the viewing directions of the sites, in terms of root‐mean‐square residuals. In the northward direction at Pisgah the estimates using either the old or new implementation disagree with the model, and might be related to an insufficiently small temporal scale used in EMPIRE.